Odpowiedź :
ile wynosi y
a) dla x=1 i
y=4x- x³/2
y=4-1/2=3 i1/2
x=3
y=4*3- 3³/2=12-27/2=12-13,5=-1,5
b) dla x=-1
y=x³/3
y=-1/3
x=2
y=8/3
c) dla x=2
y=3∛2-1
x=4
y=3∛4-1
a) dla x=1 i
y=4x- x³/2
y=4-1/2=3 i1/2
x=3
y=4*3- 3³/2=12-27/2=12-13,5=-1,5
b) dla x=-1
y=x³/3
y=-1/3
x=2
y=8/3
c) dla x=2
y=3∛2-1
x=4
y=3∛4-1
a) dla x=1
y=4x- x³/2
y=4*1-1³/2
y=4-1/2
y=3/2
dla x=3
y=4*3-3³/2
y=12-27/2
y=-15/2
b)dla x=1
y=-1³/3
y=-1/3
dla x=3
y=2³/3
y=8/3
c)dla x =2
y=3∛2-1
dla x=4
y=3∛4-1
y=4x- x³/2
y=4*1-1³/2
y=4-1/2
y=3/2
dla x=3
y=4*3-3³/2
y=12-27/2
y=-15/2
b)dla x=1
y=-1³/3
y=-1/3
dla x=3
y=2³/3
y=8/3
c)dla x =2
y=3∛2-1
dla x=4
y=3∛4-1